New international students' social information practices during transition to their host country. Issue 1 (1st February 2019) - Oh, Chiyoung; Butler, Brian S.
ABSTRACT: As newcomers, international students face information challenges in unfamiliar environments. Studies have reported that social and online resources, such as friends and the Internet, are their important sources of information, but research is less clear about how international students seek information through social sources. This paper examines social information practices of new international students in a U.S. university during adjustment to their new local environments. Also, based on prior studies, we investigate how international students' socio‐national context, specifically the degree to which there are co‐nationals in one's local environments, shapes their social information practices. Findings show that international students from common countries of origin (China, India, and Korea) developed online and mobile communities with co‐national students and shared local information among them while most international students from other less common countries did not engage in such co‐national networking and information practices. This paper suggests that information behavior theories account for people's socio‐national contexts to better inform research and practice involving internationally mobile individuals and groups.